Information Structure and Agreement - Camacho Taboada, María Victoria; Jiménez-Fernández, Ángel; Martín-González, Javier; Reyes-Tejedor, Mariano (Linguistik Aktuell/Linguistics Today, 2013)
The existing syntactic accounts of null arguments typically rely either on the specific licensing conditions for different types of empty categories such as pro and (topic-)bound variables, or else on different kinds of ellipsis. In trying to address the radical argument drop character of Catalan Sign Language (LSC), this paper critically reassesses the two main trends in the analysis of this phenomenon in East Asian languages and their extensions to American Sign Language (ASL). Both hybrid and uniform approaches to empty arguments turn out to be unable to account for the non-negligible differences observed across East Asian and sign languages. Most importantly, the availability of sloppy readings for empty arguments as a criterion to identify ellipsis vis-à-vis empty pronouns is shown to be empirically incorrect on the basis of fresh data from Catalan and English. After intensive research in this domain over the years, a satisfactory theory of null arguments that does justice to the wealth of crosslinguistic variation is still lacking.